Pola Pemberian Antimikroba pada Pasien Sepsis di RSUP Prof. Dr. R. D. Kandou Manado Periode Januari - Juni 2019 - Taroreh, Reinhard C.; Tambajong, Harold F.; Lalenoh, Diana Ch. (Universitas Sam Ratulangi, 2019)
Abstract: Sepsis is defined as organ dysfunction that threatens life due to disregulated response of vulnerable host to the infection agent. Antimicrobial therapy is one of the main therapies in the management of septic cases. Survival sepsis campaign guidelines in 2016 recommended antimicrobial administration in one hour after being diagnosed as sepsis. This study was aimed to determine the pattern of antimicrobial administration among septic patients in the Intensive Care Unit of RSUP Prof. Dr. R. D. Kandou Manado. This was an observational analytical study with a cross-sectional design. Samples were intensive care unit patients of RSUP Prof. Dr. R. D. Kandou Manado diagnosed as sepsis and its classification obtained from the Medical Record Installation data for the period of January to June 2019. The results showed a total of 35 septic patients consisting of 16 females (45.7%) and 19 males (54.3%). The time of antimicrobial administration â‰¤1 hour was found in 21 cases (60%). The most frequent antimicrobial administered was ceftriaxone in 13 cases (37.1%). The mortality rate after >48 hours was 13 cases (59%). In conclusion, most antimicrobial administration was in 1 hour after being diagnosed as sepsis and ceftriaxone was the most frequent antimicrobial given. Mortality rate after administration of antimicrobial was still high.Keywords: sepsis, ICU, antimicrobial, mortality rateÂ Abstrak: Sepsis didefinisikan sebagai disfungsi organ yang mengancam nyawa akibat disregulasi respon penjamu terhadap infeksi. Terapi antimikroba merupakan salah satu terapi utama dalam penatalaksanaan kasus sepsis. Pedoman Survival Sepsis Campaign tahun 2016 menyatakan pemberian antimikroba yang direkomendasikan ialah satu jam setelah terdiagnosiss sepsis. Penelitian ini bertujuan untuk mengetahui pola pemberian antimikroba pada pasien sepsis di Intensive Care Unit RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah analitik observasional dengan desain potong lintang. Sampel penelitian ialah pasien ICU Prof. Dr. R. D. Kandou Manado dengan diagnosis sepsis dan klasifikasinya, diperoleh dari data Bagian Instalasi Rekam Medik periode Januari-Juni 2019. Hasil penelitian mendapatkan total 35 pasien dengan diagnosis sepsis, terdiri dari 16 orang perempuan (45,7%) dan 19 orang laki-laki (54,3%). Waktu pemberian antimikroba â‰¤1 jam pada sebanyak 21 kasus (60%). Penggunaan antimikroba yang sering diberikan ialah ceftriaxone pada 13 kasus (37,1%). Angka kematian setelah >48 jam sebanyak 13 kasus (59%). Simpulan penelitian ini ialah sebagian besar pemberian antimikroba 1 jam setelah didiagnosis sepsis dengan ceftriaxone sebagai antimikroba yang paling sering diberikan. Angka kematian pasca pemberian antimikroba masih tinggi.Kata kunci: sepsis, ICU, antimikroba, angka kematian